The impact of strategic dexterity in achieving leadership performance (Czech Journal of Multidisciplinary Innovations, 2023)
The aim of the current research is to determine the effect of the independent variable, strategic ambidexterity, on Pioneering performance. A sample of Petrochina’s administrative leadership was selected, represented by (67) managers in the company. A set of programs and statistical methods were used, represented by SPSS, EXCEL, Pearson’s correlation coefficient, and Cronbach’s alpha coefficient. The independent variable, strategic ambidexterity, was measured by two dimensions: (exploration, exploitation). As for the dependent variable, represented by Pioneering performance, it was measured by a set of dimensions: (Creativity...initiative, taking risks), as the research concluded with a set of results, the most important of which was that Petrochina operates on the concept of strategic ingenuity through the expertise and administrative skills present in the research sample company, and this enables it to keep up with competition with its counterparts. The research also reached a set of recommendations, the most important of which was the need for high attention to the concept of strategic ambidexterity in the company under study by intensifying training and qualification programs for its administrative leaders and enabling them to use the available technology to a greater extent.